Spain in a State of Uncertainty - A. V. Baranov (Vestnik MGIMO-Universiteta)
Book Review: Khenkin S. 2023. Spain. Modern unstable society. Moscow. Aspect Press.Book Review: Khenkin S. 2023. Spain. Modern unstable society. Moscow. Aspect Press.